Memory's library medieval books in early modern England - Summit, Jennifer 1965- (Chicago, Ill. [u.a.] Univ. of Chicago Press, 2008)
Introduction : libraries of memory -- Lydgate's libraries : Duke Humfrey, Bury St. Edmunds, and The fall of princes -- The lost libraries of English humanism : More, Starkey, Elyot -- Reading Reformation : the libraries of Matthew Parker and Edmund Spenser -- A library of evidence : Robert Cotton's medieval manuscripts and the generation of seventeenth-century prose -- "Cogitation against libraries" : Bacon, the Bodleian, and the weight of the medieval past -- Coda : memories of libraries
Includes bibliographical references and index
Archivierung prüfen
Archivierung prüfen
Keywords: Libraries -- England -- History -- 1400-1600; Libraries -- England -- History -- 17th century; Books and reading -- England -- History -- 16th century; Books and reading -- England -- History -- 17th century; Reformation -- England; Book collecting -- England -- History; Libraries -- England -- History -- 1400-1600; Libraries -- England -- History -- 17th century; Books and reading -- England -- History -- 16th century; Books and reading -- England -- History -- 17th century; Reformation -- England; Book collecting -- England -- History; England -- Intellectual life -- 16th century